A new species of Fungitarsonemus (Acari: Prostigmata: Tarsonemidae) from Australia - Rezende, José M. [UNESP]; Otto, Jürgen C.; Lofego, Antonio C. [UNESP]; Ochoa, Ronald (Systematic and Applied Acarology Society, 2018)
Fungitarsonemus Cromroy is a genus of Tarsonemidae (Prostigmata) that is easily recognizable by the shape of its pharynx and length of the scapular setae of both sexes. Fourteen species have been described worldwide. Here, we describe Fungitarsonemus australiensis sp. nov. from citrus in Australia. A key to the species of Fungitarsonemus from Oceania is provided.
Keywords: Citrus; Heterostigmata; Prostigmata; Taxonomy